2008
DOI: 10.1021/jo801371w
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct C-2 Arylation of Indoles with Potassium Aryltrifluoroborate Salts

Abstract: Mild conditions have been developed to achieve Pd(OAc)2-catalyzed regioselective cross-coupling between indoles and potassium aryltrifluoroarylborates in the presence of Cu(OAc)2 in acetic acid at room temperature. A variety of potassium aryltrifluoroborates selectively undergo the direct arylation across indoles and afford 2-aryl indoles in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(49 citation statements)
references
References 67 publications
3
41
1
3
Order By: Relevance
“…We monitored the C3-H activation reaction by 1 H NMR spectroscopy (Table 2). In general, a C-H bond activation mechanism is used to describe the substitution of indoles by electrophilic metals such as Pd(II) [35][36][37][38]. Thus, indole 1a reacted with (η In contrast, in the absence of benzyl alcohol 2a, or when using toluene instead of 2a, only a trace amount of deuterium was incorporated (entry 2; 12%, entry 3; 14%).…”
Section: Resultsmentioning
confidence: 99%
“…We monitored the C3-H activation reaction by 1 H NMR spectroscopy (Table 2). In general, a C-H bond activation mechanism is used to describe the substitution of indoles by electrophilic metals such as Pd(II) [35][36][37][38]. Thus, indole 1a reacted with (η In contrast, in the absence of benzyl alcohol 2a, or when using toluene instead of 2a, only a trace amount of deuterium was incorporated (entry 2; 12%, entry 3; 14%).…”
Section: Resultsmentioning
confidence: 99%
“…33). 该方法适用 [70] 、芳基硅氧烷(ArSi(OR) 3 ) [71] 、芳基磺酰氯 (ArSO 2 Cl) [72] 、芳基磺酰肼(ArSO 2 NHNH 2 ) [73] 均被用作芳 基化试剂, 在 Pd 催化下与吲哚的 C2 位发生偶联反应. 随后, 施章杰、李焕荣和徐立进等 [76] 在吲哚 N 原子 上引入嘧啶导向基团, 该嘧啶基团可以引导 Rh 催化剂 活化邻位的 C-H 键.…”
Section: 吲哚直接 C-hunclassified
“…Reaction Coupling partner/reagent Catalyst References 1a rylation aryl halides Rh [25] 2P d [26,27,[31][32][33] 3a renes Pd [28][29][30] 4d iaryliodoniumsalts Pd [33,35] 5a rylboronr eagents Pd [36][37][38] 6R h, Ru [39,40] 7a rylsilanes Rh [41] 8P d [42] 9b enzoic acid Rh [43] 10 alkynylationa lkynes Pd [44] 11 alkenylationP d [46,[50][51][52]54,55] 12 alkenes Rh [48,53,59] 13 Ru [53b,60] 14 vinylcarboxylic acids Rh [61] 15 Ru [49] 16 alkynes Fe [56] 17 Co [58] 18 alkylation alkyl halides Pd [63,65] 19 Co [66] 20 Pd [70] 21 Fe [56] 22 alkenes Ir [67,71] 23 Co [69] 24 Ir [72] 25 acylationa ldehydes Pd [75] 26 Rh [76] 27 annulations Co [57] 28 Pd [77,…”
Section: Entrymentioning
confidence: 99%
“…Ther eactionc ould also be scaled up to ao ne gram scale.P d-based nanoparticles have also been shown to successfully catalyze oxidative arylation reactions. [37] Cheng and co-workers [38] exploited aryltrifluoroborate salts as coupling partners in the presenceo f Pd(OAc) 2 and Cu(OAc) 2 in air (Scheme 11). Aryltrifluoroborate salts elaborated with severely electronwithdrawing groups (such as Fo rC F 3 )o perated poorly,b ut reagents that did not possess these structural features affordedt he 2-arylindoles in mostly good yields.T he authors also studied the use of arylboronica cids as coupling partners,b ut found that they were inferior to aryltrifluoroborate saltsw ith their method.…”
Section: Scheme7arylation Of Tryptophansmentioning
confidence: 99%